Case report: A de novo NSD2 truncating variant in a child with Rauch-Steindl syndrome - Yang, Qi; Gong, Di; Yi, Shang; Luo, Jingsi; Zhang, Qinle (Frontiers in Pediatrics, 2023)
Wolf–Hirschhorn syndrome (WHS) is a rare genetic disorder caused by a heterozygous deletion on chromosome 4p16.3, which is called the WHS critical region (WHSC). The major features of this disorder, including “Greek warrior helmet” facies, delayed growth, intellectual disability, seizures, and skeletal abnormalities, are caused by the combined haploinsufficiency of multiple genes. The WHS candidate 1 (WHSC1) gene, also known as NSD2, is located in the WHSC and has been reported to associate with Rauch-Steindl syndrome (RSS,OMIM 619695). RSS is a highly heterogeneous disease characterized by mild developmental delay, prenatal-onset growth restriction, low body mass index, and characteristic facial features distinct from WHS. In this report, using whole exome sequencing (WES), we identified a novel de novo heterozygous NSD2 truncating variant in a 7-year-old Chinese girl with Rauch-Steindl syndrome, including failure to thrive, facial dysmorphisms, developmental delay, intellectual disability, and hypotonia. These findings further support that haploinsufficiency of NSD2 is necessary for WHS, and molecular genetic testing is more accurate to diagnose these patients. The novel variant uncovered in this study further expands the mutation spectrum of NSD2.